Between privacy and security: the factors that drive intentions to use cyber-security applications. Issue 16 (10th December 2021) - Chassidim, Hadas; Perentis, Christos; Toch, Eran; Lepri, Bruno
ABSTRACT: Installing security applications is a common way to protect against malicious apps, phishing emails, and other threats in mobile operating systems. While these applications can provide essential security protections, they also tend to access large amounts of people's sensitive information. Therefore, individuals need to evaluate the trade-off between the security features and the privacy invasion when deciding on which protection mechanisms to use. In this paper, we examine factors affecting the willingness to install mobile security applications by taking into account the invasion levels and security features of cyber-security applications. To this end, we propose a visual language that depicts the coverage of different security features as well as privacy intrusiveness levels. Our user study ( n =300) shows that users assessing security applications find their trade-off balance in highly secure apps with a medium level of privacy invasion. The results indicate that a low privacy invasion might signal that the security application provides less security. We discuss these findings in the context of understanding the trade-off between privacy and security.